2011
DOI: 10.1097/igc.0b013e31820e135a
|View full text |Cite
|
Sign up to set email alerts
|

Activated Leukocyte Cell Adhesion Molecule Expression Is Up-Regulated in the Development of Endometrioid Carcinoma

Abstract: The up-regulation of ALCAM expression during endometrial carcinogenesis and the correlations of ALCAM expression with grade and myometrial invasion suggest its potential role as a diagnostic and prognostic biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The possible use of sALCAM as biomarker in ovarian cancer is still to be addressed by comparisons with other gynecological diseases. In this context a recent study showed upregulation of ALCAM mRNA in endometrial carcinoma, although no data on sALCAM levels were provided 44…”
Section: Discussionmentioning
confidence: 98%
“…The possible use of sALCAM as biomarker in ovarian cancer is still to be addressed by comparisons with other gynecological diseases. In this context a recent study showed upregulation of ALCAM mRNA in endometrial carcinoma, although no data on sALCAM levels were provided 44…”
Section: Discussionmentioning
confidence: 98%
“…Although ALCAM has been implicated in these numerous pathological states, it is as yet unclear how ALCAM contributes to metastasis. Existing reports are paradoxical, with ALCAM gene expression being highly upregulated in some cancers [25], [31], [34] and greatly downregulated in others [28], [35], [36]. Unfortunately, these data are necessarily correlative in nature; therefore, an understanding of the contribution of ALCAM to cancer progression and, indeed, normal cell motility and adhesion, has been hampered by a lack of studies aimed at directly manipulating ALCAM levels within particular cell lines and determining the outcome of this manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…In order to identify an optimal target for NIRF imaging of xenograft models, selected cell surface proteins (EpCAM, activated leukocyte cell adhesion molecule (ALCAM), insulin-like growth factor 1 receptor alpha (IGF1R), and L1 cell adhesion molecule (L1CAM)) reported to be expressed in endometrial carcinoma [26][27][28][29][30][31][32][33] were screened by flow cytometry in the endometrial carcinoma cell line Ishikawa. EpCAM was found to have the highest expression, with positive staining in 99.9% of cells and a mean fluorescent intensity (MFI) fold increase of 305.3 in comparison to unstained cells ( Figure 1A, Table S1).…”
Section: Endometrial Carcinoma Cell Lines Express Epcam In Vitromentioning
confidence: 99%
“…To identify potential target molecules for NIRF imaging, databases (www.proteinatlas.org and www.uniprot.org) were searched for proteins located on the surface of endometrial carcinoma cells. Candidate proteins with reported overexpression in endometrial carcinoma compared to normal epithelium (ALCAM, EpCAM and IGF1Rα) or with positive expression associated with aggressive disease (L1CAM) were selected [26,[28][29][30][31][32][33]. Direct PE-conjugated monoclonal antibodies (Mouse Anti-EpCAM PE (clone EBA-1), PE Mouse Anti-Human CD221 (clone 1H7), PE Mouse Anti-Human CD166 (clone 3A6) (all BD Biosciences, San Jose, CA, USA) and Mouse Anti-Human CD171 Antibody (PE) (clone 03, Sino Biological Inc., Beijing, China) were purchased and tested by flow cytometry to evaluate target expression in cell lines.…”
Section: Monoclonal Antibodies For In Vitro Studiesmentioning
confidence: 99%